A new species and additional records of Lobrathium Mulsant & Rey (Coleoptera: Staphylinidae: Paederinae) from southern China - Lin, Xiao-Bin; Chen, Xi; Peng, Zhong (Zootaxa, 2022)
Lobrathium chengzhifeii Lin & Peng sp. n. (Yunnan: Mengsong) is described and illustrated. The female sexual characters of L. anatinum W.-R. Li and L.-Z. Li, 2013 are described and illustrated for the first time. Additional records of L. ablectum Assing, 2012, L. biaculeatum Assing, 2012, L. demptum Assing, 2012, L. diaoluoense W.-R. Li and L.-Z. Li, 2013, L. excisissimum Assing, 2012, L. hongkongense Bernhauer, 1931 and L. tortile F.-K. Zheng, 1988 are reported. Including the new taxa, 66 Lobrathium species are currently known from China.